2019
DOI: 10.1002/jimd.12204
|View full text |Cite
|
Sign up to set email alerts
|

Slc22a5 haploinsufficiency does not aggravate the phenotype of the long‐chain acyl‐CoA dehydrogenase KO mouse

Abstract: Secondary carnitine deficiency is commonly observed in inherited metabolic diseases characterised by the accumulation of acylcarnitines such as mitochondrial fatty acid oxidation (FAO) disorders. It is currently unclear if carnitine deficiency and/or acylcarnitine accumulation play a role in the pathophysiology of FAO disorders. The long-chain acyl-CoA dehydrogenase (LCAD) KO mouse is a model for long-chain FAO disorders and is characterised by decreased levels of tissue and plasma free carnitine. Tissue level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 32 publications
2
21
1
Order By: Relevance
“…1 A). Although in this study baseline body weights of LCAD KO mice were slightly higher when compared to the WT mice (27.9 ± 0.5 versus 26.1 ± 0.4, respectively, P = 0.0126), this is not a general finding in this animal model [ 10 , 18 , 19 ]. In the first days of the study all mice lost body weight likely due to the stress associated with single housing and the baseline echocardiography.…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…1 A). Although in this study baseline body weights of LCAD KO mice were slightly higher when compared to the WT mice (27.9 ± 0.5 versus 26.1 ± 0.4, respectively, P = 0.0126), this is not a general finding in this animal model [ 10 , 18 , 19 ]. In the first days of the study all mice lost body weight likely due to the stress associated with single housing and the baseline echocardiography.…”
Section: Resultscontrasting
confidence: 56%
“…Immunoblotting of mouse heart homogenates was performed as described in an earlier study using the same primary antibodies [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…The heart lacks enzymes for carnitine synthesis and is therefore dependent on carnitine import from the circulation via the sodium dependent organic cation transporter (OCTN2). In a recent study, it was shown that haploinsufficiency of OCTN2 in lcFAO disorder mice results in decreased free carnitine levels and subsequently decrease in tissue and plasma LCAC accumulation but does not significantly affect clinically relevant outcome parameters (hypoglycemia, heart weight or liver weight) ( Ranea-Robles et al, 2020 ). However, it should be noted that the C14:1-acylcarnitine levels were still higher in lcFAO disorder with OCTN2 haploinsufficiency when compared to wild type in heart, liver and plasma.…”
Section: Discussionmentioning
confidence: 99%
“…BNP and MYH7 are well-established markers of cardiac remodeling during pathological hypertrophy. The role of MYL1 in cardiac remodeling is unknown, but we have noted that its expression is decreased in LCAD KO hearts [14]. α-SMA is a marker to detect the presence of myofibroblasts in cardiac fibrosis.…”
Section: Cardiac Function In Lcad Ko Mice Before and After Dietary Rementioning
confidence: 92%
“…Immunoblotting of mouse heart homogenates was performed as described in an earlier study using the same primary antibodies [14]. A linear mixed effect model was used to model the echocardiography data using R.…”
Section: Immunoblot Analysismentioning
confidence: 99%